2017
DOI: 10.1136/bmjqs-2016-006028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the safety culture of care homes: a multimethod evaluation of the adaptation, face validity and feasibility of the Manchester Patient Safety Framework

Abstract: Background Understanding the cultural characteristics of healthcare organisations is widely recognised to be an important component of patient safety. A growing number of vulnerable older people are living in care homes but little attention has been paid to safety culture in this sector. In this study we aimed to adapt the Manchester Patient Safety Framework (MaPSaF), a commonly used tool in the health sector, for use in care homes and then to test its face validity and preliminary feasibility as a tool for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…Most studies ( n = 35) reported single arm intervention studies with comparison of quantitative data captured about clinical outcomes before and after the quality improvement project was carried out [ 23 57 ]. Qualitative studies were the second largest group ( n = 19) [ 12 , 23 , 27 , 30 , 58 72 ], including the following methods: participatory action research ( n = 2) [ 12 , 63 ], observational ( n = 4) [ 62 , 73 75 ], interviews ( n = 1) [ 64 ], questionnaire ( n = 1) [ 69 ]. Eleven studies were interventional studies with a comparator arm, with quantitative outcome measures, including; 8 randomised controlled trials, all of which were cluster randomised at care home level [ 76 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies ( n = 35) reported single arm intervention studies with comparison of quantitative data captured about clinical outcomes before and after the quality improvement project was carried out [ 23 57 ]. Qualitative studies were the second largest group ( n = 19) [ 12 , 23 , 27 , 30 , 58 72 ], including the following methods: participatory action research ( n = 2) [ 12 , 63 ], observational ( n = 4) [ 62 , 73 75 ], interviews ( n = 1) [ 64 ], questionnaire ( n = 1) [ 69 ]. Eleven studies were interventional studies with a comparator arm, with quantitative outcome measures, including; 8 randomised controlled trials, all of which were cluster randomised at care home level [ 76 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were not duplicate publications, but rather publications of complementary descriptions and analyses of, often complex, QI projects. The six studies were SCOPE (Safer care for older persons (in residential) environments) [ 23 , 65 , 90 ], Connect for quality [ 77 , 91 ], INTERACT (Interventions to Reduce Acute Care Transfers) [ 59 , 79 , 92 , 93 ], PROSPER (PROmoting Safer Provision of care for Elderly Residents) [ 12 , 15 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the prevailing safety culture of the homes was assessed using a version of the Manchester Patient Safety Framework (MaPSaF) 22 adapted for use in care homes. 23 The three main components of the intervention were delivered or facilitated over a six-month period in each care home by members of the local government improvement team in partnership with NHS staff and the evaluation team. A strong emphasis was placed on providing support and advice, and sharing learning between the participating homes.…”
Section: The Safety Improvement Interventionmentioning
confidence: 99%
“…An assessment of patient safety culture is the first step towards its implementation (7) in order to improve care (6) and to support service management through its monitoring, thus influencing organizational changes (3) . Such assessment initially only occurred in the hospital environment (1,(8)(9) , but in recent years its use has been increasing in long-term care facilities (8,10) , elderly homes (9) , and primary attention (1) , as it is understood that risks are present in all healthcare spheres (11) .…”
Section: Introductionmentioning
confidence: 99%